2003
DOI: 10.2460/javma.2003.222.1733
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of and complications associated with prophylactic percutaneous laser disk ablation in dogs with thoracolumbar disk disease: 277 cases (1992–2001)

Abstract: Results suggest that prophylactic percutaneous laser disk ablation is associated with few complications and may reduce the risk of recurrence of signs of intervertebral disk disease in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 20 publications
0
40
0
1
Order By: Relevance
“…With consideration for the evaluation of PLDA ' s effectiveness for prevention of disc extrusion, multiple sites will be easily accomplished as compared to other surgical techniques without the potential concerns with regard to patient morbidity and prolonged anesthetic times. Bartels et al [16] have also demonstrated that the risk encountered in obtaining such evidence is low as minimal complication was observed. Therefore pursuit of higher levels of evidence with regard to PLDA and IVDD is unequivocally necessary.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…With consideration for the evaluation of PLDA ' s effectiveness for prevention of disc extrusion, multiple sites will be easily accomplished as compared to other surgical techniques without the potential concerns with regard to patient morbidity and prolonged anesthetic times. Bartels et al [16] have also demonstrated that the risk encountered in obtaining such evidence is low as minimal complication was observed. Therefore pursuit of higher levels of evidence with regard to PLDA and IVDD is unequivocally necessary.…”
Section: Discussionmentioning
confidence: 96%
“…One must consider, however, that follow-up times for cases having undergone spinal decompression for intervertebral disc extrusion should be nearly 3 years as suggested by Mayhew et al [22] . With consideration to the criteria for inclusion in the study by Bartels et al [16] , one can infer that follow-up times were approaching acceptable ranges due to the fact that dogs were included if a documented history of thoracolumbar IVDD was present along with treatment and complete recovery. Unfortunately, the areas in which this study and others are evaluation and plain radiography.…”
Section: Critical Analysis Of the Available Evidencementioning
confidence: 99%
See 3 more Smart Citations